Punishing status and the punishment status quo: Solitary confinement in U.S. Immigration prisons, 2013–2017 - Franco, Konrad (Punishment & society, 2022)
This study provides the first systematic, nationally representative analysis of administrative records of solitary confinement placements in any carceral setting. We examine patterns in who experiences solitary confinement in Immigration and Customs Enforcement (ICE) custody, as well as the stated reason for, and length of, their confinement. We reveal several findings. First, cases involving individuals with mental illnesses are overrepresented, more likely to occur without infraction, and to last longer, compared to cases involving individuals without mental illnesses. Second, solitary confinement cases involving immigrants from Africa and the Caribbean are vastly overrepresented in comparison to the share of these groups in the overall detained population, and African immigrants are more likely to be confined for disciplinary reasons, compared to the average. Finally, placement patterns vary significantly by facility and institution type, with private facilities more likely to solitarily confine people without infraction, compared to public facilities. This study offers a lens through which to more precisely theorize the legal boundary-blurring of crimmigration and the relationship between prison and immigration detention policies, to better understand the practice of solitary confinement across carceral contexts, and to analyze the relationship between national-level policy and on-the-ground implementation.